2000
DOI: 10.1007/pl00000199
|View full text |Cite
|
Sign up to set email alerts
|

Differential anti-inflammatory effects of immunosuppressive drugs: Cyclosporin, rapamycin and FK-506 on inducible nitric oxide synthase, nitric oxide, cyclooxygenase-2 and PGE2 production

Abstract: These studies characterize differential mechanistic capacity of the immunophilin-binding immunosuppressive drugs (comparable to hydrocortisone) to inhibit both iNOS and COX-2 expression. Inhibition of iNOS and COX-2 mRNA accumulation by cyclosporin and rapamycin seem to be distinct. These studies also highlight potential anti-inflammatory properties of these drugs in addition to their known immunosuppressive activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 63 publications
1
77
0
Order By: Relevance
“…Additionally, a recent provocative report demonstrated that cyclosporine directly influenced respiratory epithelial cells to secrete factors that enhance fibroblast proliferation (41). Although it is not known what factors were liberated that promoted fibroblast proliferation in this study, cyclosporine inhibition of PGE 2 release could culminate in airway fibrosis (41)(42)(43)(44)(45). Therefore, it has been postulated that the influence of cyclosporine on epithelium could contribute to the development of fibrotic lung disease (obliterative bronchiolitis) after lung transplantation (41).…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, a recent provocative report demonstrated that cyclosporine directly influenced respiratory epithelial cells to secrete factors that enhance fibroblast proliferation (41). Although it is not known what factors were liberated that promoted fibroblast proliferation in this study, cyclosporine inhibition of PGE 2 release could culminate in airway fibrosis (41)(42)(43)(44)(45). Therefore, it has been postulated that the influence of cyclosporine on epithelium could contribute to the development of fibrotic lung disease (obliterative bronchiolitis) after lung transplantation (41).…”
Section: Discussionmentioning
confidence: 79%
“…Rapamycin inhibits tumor growth by not only suppressing angiogenesis (49) but also preventing the proliferation of cancer cells (50). Moreover, rapamycin enhanced the apoptosis of chemotherapy-resistant tumor cells (34) and reduced inflammation by regulating arginase, iNOS, and ROS (35,36). In MDSCs, rapamycin enhanced gemcitabine-induced apoptosis in vitro (C.-Y.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to find a chemical inhibitor that regulates FKBP51 function for more in-depth analysis of the role of FKBP51 in MDSCs, and several reports demonstrated that FK506 and rapamycin inhibit the peptidyl-prolyl isomerase (PPIase) function of FKBP51 (33,34) and regulate inflammation (35,36). Thus, we tested whether FK506 and rapamycin could inhibit the suppressive activity of MDSCs.…”
Section: A Chemical Inhibitor Of Fkbp51 Rapamycin Reduces the Supprmentioning
confidence: 99%
“…[85][86][87][88][89][90] In addition, sirolimus has been shown to inhibit VEGF-induced microvascular permeability, and reduces protein kinase C (PKC) activity, [85][86][87][88][89][90][91] as well as reduces the expression of inflammatory cytokines. 92,93 Recently, a phase 1 study of subconjunctival and intravitreal sirolimus in DMO was reported by Dugel et al 94 No non-ocular adverse events were noted, and the systemic exposure to sirolimus was low. There were no serious ocular adverse events reported.…”
Section: Angiopoietin (Ang)-2 Blockagementioning
confidence: 99%